Designing an Internet of Things-Based Automatic Door Lock System Using Esp32 Cam, Keypad, Fingerprint with Telegram Notifications at PT. Hosana Inti - Icha Novalita Nainggolan; Ratih Ade Verlina Simbolon (Journal Majelis Paspama, 2025)
This study aims to design and build an Internet of Things (IoT)-based automatic door lock system using ESP32 Cam, keypad, and fingerprint sensor equipped with notifications via the Telegram application at PT. Hosana Inti. The development method used is a prototype model, which includes the stages of requirements gathering, hardware and software design, prototype development, and system evaluation and improvement. This system utilizes dual authentication in the form of fingerprint and PIN to enhance access security. The ESP32 Cam captures images of users every time the door is opened and sends them to a specified Telegram account in real time. Test results show that the system works as designed: the door can be opened through fingerprint or PIN authentication, and notifications along with user photos are successfully sent to Telegram. The main obstacles found are the sensitivity of the fingerprint sensor and network connection stability. Overall, this system can be a practical and efficient security solution for companies and homes, with the potential to develop access data storage features to improve monitoring.